Ethics in public management (Legal journal - Research in Legal and Social Sciences, 2017)
Corruption in society and in States constitutes one of the serious issues that arise in public law. There is no doubt that corruption is not a phenomenon of today. Seneca wrote many centuries ago that corruption is a vice of men, not of the times: “Human weakness – he affirmed – will always be present among us; mistakes can always be made, and the corrupt will look for new ways to play with the system” Although the phenomenon is as old as man himself, it has been in recent times that there has been concern about it, both in the private sphere and in the public sphere. the public, because corruption is closely linked to power, to all power, political and economic. There has been a multiplication of state, supra-state and local regulations, recommendations and deontological codes, congresses, conferences, forums and meetings, and works of denunciation, proposals for measures to deal with and remedy the prevailing situation with respect to to corruption. As the ethical values ​​in force in general in each country have diminished, they must be redefined. In short, the codes of Ethics are erected in the new ethical norms, what is proposed are paradigms of conduct for each organization, which must constitute the written expression of an ethos that is part of the corporate culture of the organization. Rules that everyone must respect, that must be enforced.
Keywords: public function; public law; corruption; public management; Ethics